Exome Sequencing Implicates SWI/SNF Chromatin Remodeling Genes in Human Congenital Hydrocephalus. (1st September 2019) - Allocco, August A; Jin, Sheng Chih; Dong, Weilai; Zeng, Xue; Conine, Sierra B; Furey, Charuta Gavankar; Date, Priya Prakash; Gaillard, Jonathan; Nelson-Williams, Carol; Dunbar, Ashley; DeSpenza, Tyrone; Deniz, Engin; et al.
Abstract: INTRODUCTION: Congenital Hydrocephalus (CH) affects 1 in 1000 live births and is treated with lifelong surgical cerebrospinal fluid (CSF) diversion with substantial morbidity. Our group recently sequenced 180 probands with CH and identified 4 novel CH genes, all of which regulate neural stem cell (NSC) fate. Nonetheless, these genes account for just 10% of studied cases. METHODS: We doubled the size of our cohort through robust recruitment and exome-sequenced 361 CH probands, including 216 case-parent trios. To study the effect of novel mutations on brain development, we developed a Xenopus tropicalis model of CH using CRISPR/Cas9. Multiple, nonoverlapping CRISPR guide RNAs targeted against candidate genes were designed and injected into fertilized single cell Xenopus embryos via microinjection. Ventricular morphology and CSF flow dynamics were analyzed via optical coherence tomography (OCT) imaging. Histological sections from WT and mutant Xenopus embryos were subjected to whole-mount in Situ hybridization to assess expression of various markers of NSC growth and proliferation. RESULTS: We identified new causative mutations in both previously identified and novel genes, all of which regulate ventricular zone NSC fate. Of these, enrichment in rare, damaging variants was highest in the SWI/SNF chromatin remodeling complex genes SMARCC1 and ARID1B ( P  = 1.83 × 10-9). Xenopus tadpoles harboring mutations in SMARCC1 exhibited marked ventriculomegaly, aqueductal stenosis, and impaired CSF flow. In Situ hybridization of SMARCC1 knockout brain sections demonstrated decreased expression of genes regulating NSC growth and proliferation. Notably, injection of wild type SMARCC1 RNA restored normal brain development in SMARCC1 KO embryos. CONCLUSION: These findings implicate SWI/SNF complex genes in CH and validate the use of Xenopus for investigating additional candidate genes. These findings highlight the importance of NSC dysregulation in CH pathology, and suggest that in a subset of patients the risk of adverse neurodevelopmental outcomes may be unaltered whether or not shunting is performed.